The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1155/2023/4509889
|View full text |Cite
|
Sign up to set email alerts
|

A Compound Class of Unit Burr XII Model: Theory, Estimation, Fuzzy, and Application

Abstract: The current research offers an enhanced three-parameter lifetime model that combines the unit Burr XII distribution with a power series distribution. The novel class of distribution is named the unit Burr XII power series (UBXIIPS). This compounding technique allows for the production of flexible distributions with strong physical meanings in domains such as biology and engineering. The UBXIIPS class includes the unit Burr XII Poisson (UBXIIP) distribution, the unit Burr XII binomial distribution, the unit Bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…The first dataset was used in Fayomi et al [29] and represented a random sample of Saudi Arabia's COVID-19 mortality rates over a 36-day period. The second dataset was used in Zayed et al [30] and showed the total milk production from the first birth of 107 cows of the SINDI race. To ensure the reliability and suitability of this study, we used different sample sizes.…”
Section: Empirical Studymentioning
confidence: 99%
“…The first dataset was used in Fayomi et al [29] and represented a random sample of Saudi Arabia's COVID-19 mortality rates over a 36-day period. The second dataset was used in Zayed et al [30] and showed the total milk production from the first birth of 107 cows of the SINDI race. To ensure the reliability and suitability of this study, we used different sample sizes.…”
Section: Empirical Studymentioning
confidence: 99%